2013
DOI: 10.3852/12-395
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocosmospora, a new genus to accommodate Cosmospora vilior and related species

Abstract: Cosmospora sensu Rossman accommodated nectroid fungi with small, reddish, smooth, thin-walled perithecia but recently was found to be polyphyletic and has been segregated into multiple genera. Not all cosmospora-like fungi have been treated systematically. Some of these species include C. vilior and many specimens often labeled "Cosmospora sp." The objectives of this research were to establish the identity of C. vilior through epitypication using a recent collection that agrees with the type specimen in morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The occurrence of Pseudocosmospora rogersonii was unexpected, as it is reported to be a parasite of only Eutypella sp. (Ascomycota: Xylariales) [76]. In this study, we reported the presence of Pseudocosmospora rogersonii for the first time outside of the USA.…”
Section: Discussionmentioning
confidence: 62%
“…The occurrence of Pseudocosmospora rogersonii was unexpected, as it is reported to be a parasite of only Eutypella sp. (Ascomycota: Xylariales) [76]. In this study, we reported the presence of Pseudocosmospora rogersonii for the first time outside of the USA.…”
Section: Discussionmentioning
confidence: 62%
“…Thirteen species were selected based on the availability of host data. Sequences were generated in prior taxonomic work (Herrera et al 2013(Herrera et al , 2015. Briefly, DNA was extracted from mycelium grown for 1 week in Difco TM potato dextrose broth with PowerPlant â DNA Isolation Kit (MO BIO Laboratories Inc., Solana Beach, CA).…”
Section: Cosmospora Phylogenymentioning
confidence: 99%
“…; Herrera et al. ). The sexual fruiting bodies (perithecia) in Cosmospora sensu lato (hereafter “ Cosmospora ‐like”) are highly conserved to the degree of being indistinguishable.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Gräfenhan, Seifert & Schroers, Microcera Desm., Pseudocosmospora C. Herrera & P. Chaverri, Stylonectria and Volutella Fr. (Schoch et al 2000;Zhuang 2010a, 2012;Gräfenhan et al 2011;Herrera et al 2013;Lombard et al 2015).…”
Section: Introductionmentioning
confidence: 97%